Challenges and guidelines for integrated water management in river basins: an expert view - Cerezini, Monise Terra; Hanai, Frederico Yuri (Sustainability in Debate, 2023)
Integrated Water Resources Management (IWRM) is a widely accepted approach that requires technical, political, and institutional structuring for its effective implementation. An Expert Panel was created to identify Brazil’s primary challenges and guidelines for water management. The participants’ opinions indicated that most of the issues identified reached an agreement of 70% or higher. Among these challenges, education and participation were frequently cited by experts as central concerns. These themes were also recognised as crucial factors in addressing the challenges related to water resource management and ensuring the successful execution of the National Water Resources Policy.